2007
DOI: 10.1152/ajpregu.00261.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic elevated carbon dioxide on the expression of acid-base transporters in the neonatal and adult mouse

Abstract: Several pulmonary and neurological conditions, both in the newborn and adult, result in hypercapnia. This leads to disturbances in normal pH homeostasis. Most mammalian cells maintain tight control of intracellular pH (pH(i)) using a group of transmembrane proteins that specialize in acid-base transport. These acid-base transporters are important in adjusting pH(i) during acidosis arising from hypoventilation. We hypothesized that exposure to chronic hypercapnia induces changes in the expression of acid-base t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 69 publications
3
22
0
3
Order By: Relevance
“…Instead, the slow increase in NHE-1 mRNA in sea bass kidney during chronic hypercapnia (96 h) was consistent with results of studies in mammals that showed an increase in NHE-1 messenger during chronic metabolic acidosis in the kidney cortex (Soleimani et al 1995). Moreover, a recent scientific publication reported a significant increase in acid extruder protein levels (among which is NHE-1) and a decrease in acid loader proteins in kidney, brain, and heart of mice exposed to chronic hypercapnia; This is considered an adaptive response to attenuate intracellular acidosis induced by hypercapnia in this animal (Kanaan et al 2007).…”
Section: Time Points Testedsupporting
confidence: 91%
“…Instead, the slow increase in NHE-1 mRNA in sea bass kidney during chronic hypercapnia (96 h) was consistent with results of studies in mammals that showed an increase in NHE-1 messenger during chronic metabolic acidosis in the kidney cortex (Soleimani et al 1995). Moreover, a recent scientific publication reported a significant increase in acid extruder protein levels (among which is NHE-1) and a decrease in acid loader proteins in kidney, brain, and heart of mice exposed to chronic hypercapnia; This is considered an adaptive response to attenuate intracellular acidosis induced by hypercapnia in this animal (Kanaan et al 2007).…”
Section: Time Points Testedsupporting
confidence: 91%
“…It has been well established that cells rely on ionic transporters and exchangers to modulate both intracellular and extracellular pH (23,26,38,48). Much of this work has focused on a specific class of acid-base transporters, the sodium-proton exchangers (NHE).…”
Section: Discussionmentioning
confidence: 99%
“…1D,E; supplementary material Movie 4). These experiments emphasize that the presence of carbonate is important for many cellular processes, such as those related to the actions of Cl -and Na + exchangers, as well as co-transporters (Kanaan et al, 2007), and is not simply required to buffer the medium (Casey, 2006). All media should be supplemented with 25 mM HEPES to avoid adverse effects on cells due to pH changes, which can occur after approximately 5 minutes in the absence of CO 2 (not shown).…”
Section: Mediamentioning
confidence: 99%